2021
DOI: 10.1038/s41416-020-01211-x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of an association between gallstone disease and bilirubin levels with risk of colorectal cancer: a Mendelian randomisation analysis

Abstract: Background Epidemiological studies of the relationship between gallstone disease and circulating levels of bilirubin with risk of developing colorectal cancer (CRC) have been inconsistent. To address possible confounding and reverse causation, we examine the relationship between these potential risk factors and CRC using Mendelian randomisation (MR). Methods We used two-sample MR to examine the relationship between genetic liability to gallstone disease an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Studies have reported inconsistent results regarding the relationship between circulating bilirubin levels and risk of CRC. In a Mendelian randomization study (67878 cases), TBIL levels were not associated with the risk of CRC[ 11 ], which was similar to the findings of a meta-analysis and a prospective survey[ 12 , 13 ]. In an approximately 10-year follow-up study by He et al [ 14 ], baseline TBIL levels were found to be negatively correlated with the risk of CRC.…”
Section: Discussionsupporting
confidence: 67%
“…Studies have reported inconsistent results regarding the relationship between circulating bilirubin levels and risk of CRC. In a Mendelian randomization study (67878 cases), TBIL levels were not associated with the risk of CRC[ 11 ], which was similar to the findings of a meta-analysis and a prospective survey[ 12 , 13 ]. In an approximately 10-year follow-up study by He et al [ 14 ], baseline TBIL levels were found to be negatively correlated with the risk of CRC.…”
Section: Discussionsupporting
confidence: 67%
“…The sample size of exposure and outcome ranged between 1475 and 898 130 and between 1475 and 706 031, respectively (Table S3). The causal factors can be classified into eight categories: anthropometric characteristics and obesity‐related biomarkers ( n = 31), 7–16 lifestyle habits ( n = 15), 9,10,17–21 blood micronutrients ( n = 36), 10,22–31 blood fatty acids (FAs) and lipids ( n = 43), 10,24,32–37 inflammatory biomarkers ( n = 14), 10,38–42 pathological conditions and related biomarkers ( n = 30), 10,43–50 reproductive factors ( n = 12), 10,51,52 and other biomarkers ( n = 9) 10,53–57 (Table 1, Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…three studies 46,47 but not in another, 10 and the largest one reported an OR (95% CI) of 1.11 (1.01-1.22). 47 Furthermore, no associations were found for a homeostatic model assessment for beta-cell function (HOMA-B), 45 homeostatic model assessment for insulin resistance (HOMA-IR), 48 glycosylated hemoglobin A1c (HbA1c), 45 HbA, 10 fasting glucose, 10,43,45,48 fasting insulin, 43,48 fasting proinsulin, 10 gallstone disease, 49 and bilirubin 49,50 (Table 1, Figures 2 and 3, Figure S6).…”
Section: Gallstonementioning
confidence: 99%
“…So far, CORSA contributed to multiple international consortia such as Genetics and Epidemiology of Colorectal Cancer Consortium (GECCO) [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], COlorectal cancer GENeTics (COGENT) and COnsortium of METabolomics Studies (COMETS) [ 13 ]. Furthermore, CORSA was a partner in two ERANET-TRANSCAN-funded projects: MetaboCCC [ 11 , 12 , 44 , 45 , 46 , 50 , 51 ], and “Biomarkers related to folate-dependent metabolism in colorectal cancer recurrence and survival” (FOCUS) [ 35 , 36 ]. These interdisciplinary projects bring together multiple European CRC cohorts, including CORSA, the ColoCare study of the German Cancer Research Center in Heidelberg [ 14 ], the EnCoRe study of Maastricht University, the Netherlands [ 15 ], as well as the COLON study of Wageningen University, the Netherlands [ 16 ].…”
Section: Discussionmentioning
confidence: 99%